Characteristics of cost-efficient fertilization plans at the farm level. Issue 1 (31st December 2022) - Tröster, Michael Friedrich; Sauer, Johannes
ABSTRACT: Fertilization accounts for a significant share of the costs of crop production. Farmers therefore aim to find cost-efficient fertilization plans, which is a complex and recurring optimization problem. This study analyses whole-farm fertilization plans to generate a deeper economic understanding of cost-efficient fertilization plans on farm level. Various fertilizer plans, obtained by a choice experiment, were grouped into "cost-efficient", "average" and "cost-inefficient" solutions, using cluster analysis. Group differences were analysed by t-test to reveal the characteristics of cost-efficient solutions. In addition, the fertilizer optimization system IoFarm was used to simulate the effects of extreme changes in farm constellations on the fertilizer plan. Our results show that certain fertilizers are significantly more common in cost-efficient fertilizer plans: diammonium phosphate covers 81.8% of the phosphorus and 21.7% of the nitrogen supply; granular potash covers 100% of the potash supply. Compared to cost-efficient fertilizer plans, inefficient ones have higher annual surpluses of sulphur (+45.4 kg ha −1 ) and potash (+9.8 kg ha −1 ), incurring costs and impacting sustainability. Application costs represent a proportion of 5.2% of total costs, but play a minor role compared to other factors. Fertilizer prices were identified as the largest factor influencing the fertilizer plan. The results show that cost-efficient fertilizer plans are at the same time more sustainable, which also demonstrates the societal benefit of this study. The study provides a new and important contribution to the understanding of cost-efficient fertilizer plans at the farm level. Farmers benefit significantly from this contribution, as it shows opportunities to increase cost-efficiency.